Morphology and morphometry of frontal sinuses as a tool in sex determination based on 17th–18th century skulls from Poland - Mrożek, Kamil; Marchewka, Justyna; Borowska, Beata; Budnik, Alicja; Leszczyński, Bartosz; Wróbel, Andrzej; Wronka, Iwona (Anthropological Review, 2024)
Morphological analysis of the frontal sinuses (FS) is one of the methods used to assess the sex of human remains. Depending on the methods, the results indicate the effectiveness of using the FS in the assessment of sex at the level of 60–85.9%. Our goal was to determine whether the morphological and morphometric methods of sex assessment based on the FS can be used for examining historical populations in anthropological studies. We assessed FS both morphologically and morphometrically on a sample of 76 dry skulls (41 females and 35 males) from 17th–18th century form Poland to evaluate the potential of applying this method for sex estimation in human remains. A total of 76 X–rays were taken in both frontal and lateral views. The morphology and morphometry of the FS were assessed with ImageJ software. There were no significant differences between the sexes in assessing the outline of the upper border of the FS, as well as the number of partial septa. There was a statistically significant difference between the sexes in the width of the right FS, the height of the right and left FS, and the right and left area of the FS. The lateral view indicated a statistically significant difference between the sexes regarding the depth and area of the FS. The accuracy rate in classifying males and females using FS morphometry ranged from 59.09% to 69.57%. The FS in the lateral view (69.57%) and the height of the left FS in the frontal view (68.18%) are the most appropriate regressors for sex determination. Statistically significant differences in some FS measurements between the sexes do not appear to be a sufficient indicator of sex. Morphological and morphometrical characteristics of the FS should not be used as a guideline for sex assessment in the historical Polish population.